DEGENERATIVE CHANGES IN THE CERVICAL SPINE - Kilichov Jaloliddin Gulturovich; Akhtamova Shahlola Erkinjonovna; Ibragimova Noila Mustafo kizi; Urolov Javlonbek Yuzboy o’g’li; Kasimov Arslanbek Atabayevich; Mamurova Mavludakhon Mirkhamzayevna (Western European Studies, 2024)
The diagnosis of “cervical osteochondrosis” is often made if a person complains of neck pain. Some also attribute dizziness, memory loss, numbness of the hands and other unpleasant symptoms to it. It is mistakenly believed that the disease is associated with wear and age-related deformation of the intervertebral discs and other elements of the spinal column.
Keywords: Free radical oxidation; neurodegenerative diseases; epilepsy